The Use of Spinning Wheel Media and Its Impact on Students' Career Planning Skills - Zuhara, Evi; Khaira, Wanty; Husna, Naziratul (IKIP Siliwangi, 2025)
At the level of career planning at MTsN 2 Aceh Besar, some students still cannot determine career planning after graduating from MTsN and want to look for career information. As a result, it has an impact on the student's future. This research aims to know how the spinning wheel media improves students' career planning abilities at MTsN 2 Aceh Besar. This quantitative research method uses a pre-experimental approach with a group Pretest-Posttest Design. The sample consisted of 32 students from 211 populations using purposive sampling techniques. The data collection technique uses a Likert scale to measure students' level of career planning. The questionnaire was distributed to class IX students at MTsN 2 Aceh Besar. The research results show that the t count of 51.414 is greater than the t table of 1.695 (51.414>1.695). This means there is an increase in students' career planning, so the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. The research contributes as reference material for further research on the application of spinning wheel media to improve students' career planning. Also, it serves as a guide for students in determining career planning when choosing secondary schools and career descriptions in the future.